1987
DOI: 10.1002/app.1987.070330228
|View full text |Cite
|
Sign up to set email alerts
|

Factors effecting a loss of flocculation activity of polyacrylamide solutions: Shear degradation, cation complexation, and solution aging

Abstract: SynopsisPolyacrylamide and poly(acrylamide-co-acrylic acid) flocculant solutions were subjected to Shear degradation in a rotating cone instrument. At constant shear rate, shear degradation was minimid (highat limiting intrinsic viscosity) by the use of a lower solution concentration and high ionic strength of the polymer solution. Resistance to shear degradation also increased with increasing anionic character of the polyacrylamide. Sheared polymers showed reduced performance as flocculants of coal preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 1 publication
2
20
1
Order By: Relevance
“…The main conclusion that can be drawn from these results is that the PHPA fluid, at least under the test conditions described herein, did not display an initial rapid reduction in viscosity as described by some previous researchers (Kulicke and Kniewske, 1981;Shyluk and Stow, 1969). Rather, the viscosity-time profiles shown by tests 1 and 2 are more in line with those reported by Henderson and Wheatley (1987) and to a lesser extent those by Gardner et al (1978). The cause of the gradual reduction in viscosity is possibly a conformational change of the polymer molecules leading to chain disentanglement as suggested by Narkis and Rebhun (1966).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The main conclusion that can be drawn from these results is that the PHPA fluid, at least under the test conditions described herein, did not display an initial rapid reduction in viscosity as described by some previous researchers (Kulicke and Kniewske, 1981;Shyluk and Stow, 1969). Rather, the viscosity-time profiles shown by tests 1 and 2 are more in line with those reported by Henderson and Wheatley (1987) and to a lesser extent those by Gardner et al (1978). The cause of the gradual reduction in viscosity is possibly a conformational change of the polymer molecules leading to chain disentanglement as suggested by Narkis and Rebhun (1966).…”
Section: Resultssupporting
confidence: 87%
“…These range from an initial rapid decline in viscosity (Kulicke and Kniewske, 1981;Shyluk and Stow, 1969), through negligible change (Mächtle, 1982), to a significant rise in viscosity (Likos et al, 2004). Other behaviours such as a slow decline (Henderson and Wheatley, 1987) and an inverted V-shape viscosity profile (Gardner et al, 1978) also have been reported. As the sample preparation procedures, test methods and the materials used for these studies vary considerably, it is not possible to draw any consistent conclusions that can be applied in civil engineering.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, early studies 1,2 observed decreasing solution viscosities with time. A closer examination showed that PAAm solutions experienced a rapid increase in viscosity to a maximum after 24 h, before a slower viscosity decrease to a local minimum after 160 to 180 h. 3 Explanations for viscosity changes have included chain scission due to the action of residual catalyst 2,4,5 or microorganisms, 6 crosslinking, scattering studies. 10,11 Biocides have been shown to have little effect, 11 while hydrolysis and crosslinking have only been observed at elevated temperatures.…”
Section: Introductionmentioning
confidence: 97%
“…Flocculation is a complex process and the flocculation efficiency is significantly dependent on a variety of factors, including but not limited to pH and ionic strength of the solution, agitation rate, particle size, charge density, molecular weight and dosage of the polymer. 10, 46,47 In addition, the mineral composition, and type and addition sequence of the flocculating agents also play an important role in successful destabilization of the colloidal particles. 9 Any attempt at comparing these flocculants against one another would be inadequate as there are many inconsistencies in flocculation performance analysis across different studies.…”
Section: Other Modified Natural Polymersmentioning
confidence: 99%